2005
DOI: 10.1158/1055-9965.epi-05-0077
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Risk of Non-Hodgkin's Lymphoma—A Population-Based Case-Control Study

Abstract: Background: Epidemiologic evidence of an association between tobacco smoking and non-Hodgkin's lymphoma has been conflicting. This may reflect that non-Hodgkin's lymphoma comprises several distinct disease entities with different etiologies, as some studies have indicated an association between smoking and follicular lymphoma. Objective: To investigate the association between cigarette smoking and non-Hodgkin's lymphoma risk, overall and by subtype. Methods: As part of a nationwide Danish-Swedish population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 54 publications
3
20
2
2
Order By: Relevance
“…14,16,19,30,38,40,42,43,55 Our results were also in accordance with the Interlymph findings in so far as in the pooled analysis no protective effect of alcohol was observed for European centers. 47 Similarly, the findings of the 2 other studies reporting an inverse association between alcohol intake and development of overall NHL were not based on European study populations, as one was a case-control study carried out in Japan 24 and the other one was a large American cohort study.…”
Section: Discussionsupporting
confidence: 92%
“…14,16,19,30,38,40,42,43,55 Our results were also in accordance with the Interlymph findings in so far as in the pooled analysis no protective effect of alcohol was observed for European centers. 47 Similarly, the findings of the 2 other studies reporting an inverse association between alcohol intake and development of overall NHL were not based on European study populations, as one was a case-control study carried out in Japan 24 and the other one was a large American cohort study.…”
Section: Discussionsupporting
confidence: 92%
“…Although several studies have reported no association between smoking and the risk of lymphoma (3,10,11), the pooled analysis of the International Lymphoma Epidemiology Consortium study revealed a positive association between smoking and the risk of non-Hodgkin's lymphoma [OR (95% CI), reference for never smokers and 1.07 (1.00-1.15) for ever smokers], suggesting that smoking has carcinogenic effects (9). Consistent with this, our present study also showed a positive association between smoking exposure and lymphoma [OR (95% CI), reference for never smokers and 1.24 (1.02-1.51) for ever smokers] along with heterogeneity of this risk between each of the major histologic subtypes: follicular lymphoma, Hodgkin's lymphoma, marginal zone lymphoma, and diffuse large B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several case-control and cohort studies have investigated the association of alcohol intake and smoking with the risk of Hodgkin's and non-Hodgkin's lymphoma in nonAsian populations, with most suggesting an inverse association for alcohol consumption with the risk of malignant lymphoma (1-6) versus inconsistent results for smoking (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, little research has been conducted in Asian populations, particularly with regard to the effects of smoking and alcohol consumption on the risk of malignant lymphoma subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports have shown no excess risk of NHL overall in tobacco or cigarette smokers [134 Á/137], but there are several exceptions [138Á/140]. Some studies have suggested a specific association with risk of the common follicular NHL subtype [139,141,142]. Tobacco smoking appears to induce the bcl-2 oncogene translocation (14;18) in peripheral lymphocytes of healthy individuals [143].…”
Section: Tobacco Smokingmentioning
confidence: 99%